HUBUNGAN TINGKAT KECEMASAN DENGAN KADAR GULA DARAH PADA PASIEN PRE GENERAL ANESTESI DI RSUD KOTA YOGYAKARTA - Imsakul Fatimah; Induniasih Induniasih; Rosa Delima Ekwantini (Poltekkes Kemenkes Yogyakarta, 2017)
The general anesthesia is one of the causes of anxiety. Anxiety is the body's psychological response as a reaction to threats. Anxiety can increase levels of cortisol and catecholamines so that increase of gluconeogenesis which causes hyperglycemic. Hyperglycemic cause delayed in surgery or retard of recovery time. The purpose of this research is to know corelation of anxiety rate with blood glucose level in pre general anesthesia patients at RSUD Kota Yogyakarta. This research is a quantitative research with cross sectional research design. The sample of this study amounted to 53 respondents pre general anesthesia. Sampling technique used consecutive sampling, the test used Kendall Tau test. The most common pre anesthesia respondents were moderate anxiety with 37 (69.8%) and normal blood glucose level with 51 (96.2%). Result of statistical test by Kendall Tau get significant corelation with p-value equal to 0,010 (<0,05) with low closeness relation that is 0,343. There is a corelation between anxiety rate with blood glucose level in pre general anesthesia patients at RSUD Kota Yogyakarta.